Use of the Cone Penetration Test to Derive Parameters for Shallow Foundation Design - O'Kelly, Brendan (My University, 2005)
Given the problems associated with sampling cohesionless soils there is movement towards the use of high quality in-situ tests either to derive soil parameters for use in conventional design me-thods or through the use of empirical design correlations. This paper describes a field test of a model vertically loaded footing tested at a dense sand test site. The ultimate capacity and load-displacement response at working stresses are shown to be predicted reasonably accurately using simple tech-niques which use the Cone Penetration Test (CPT) cone resistance qc as an input parameter.
Invited presentation at the International Conference on Soil-Structure Interaction: Calculation Methods and Engineering Practice
PRESENTED
Saint Petersburg, Russia
Keywords: Cone Penetration Test